Logan's choice - MacAndrew, Richard (Cambridge English readers. Level 2, 2000)
"I'm Inspector Logan of the Edinburgh police", Jenny said. "I'm very sorry about the death of your husband." Who killed Alex Maclennan? His friend, his wife, or her brother? It isn't easy, but Logan has to choose